Excellent Pharmacist Service Strategy in the Pharmaceutical Community Towards Superior and Progressive Pharmacy - Anindya Salsabila; Ranatri Puruhita; Siti Nadhira Indah P.I; Parwati; Siti Sitatul Mar’ah; Muthoifin; Muchammad Taufiq Affandi; Jihan Husna Srifyan; Ishmah Afiyah (Solo International Collaboration and Publication of Social Sciences and Humanities, 2023)
The purpose of this study is to determine the implementation of good and bad pharmaceutical ethics. The methods used are population and sample, sampling techniques, operational definitions, research instruments, data collection techniques, and data analysis. The results of research related to the implementation of practices based on SPKA as a whole can be used as studies and inputs in addition to the results of supervision from the government so that the government together with IAI professional organizations can support pharmacists in implementing practices according to standards. Decisions can also be taken appropriately by stakeholders in providing guidance, supervision and follow-up on the implementation of standards by pharmacists in pharmacies. Pharmacists can get full support to raise awareness of legal compliance in carrying out responsible practices.